Motivational Factors Across Three Generations of Women Committed to Religious Life. Issue 3 (2nd July 2016) - Kreis, Maria Clara; Crammond, Joanna; Lunz, Marcia
ABSTRACT: This interdisciplinary (spirituality/psychology/sociology) study explores the motivation of women entering and remaining in religious life from 1, 116 Roman Catholic Sisters who responded to an open-ended questionnaire. A noteworthy pattern was the tendency to cite inner call, which increased in recent generations while the tendency to cite Sisters example decreased. The vast majority of Sisters cited their commitment to God and their religious community as motivation to remain in religious life. The results indicate the importance for Sisters to live out their mission (nationally/internationally) through public service, faith formation, and as advocates by providing role models and inspiration for future Sisters.